2007
DOI: 10.5194/angeo-25-1531-2007
|View full text |Cite
|
Sign up to set email alerts
|

Daytime F2-layer negative storm effect: what is the difference between storm-induced and Q-disturbance events?

Abstract: Abstract. Negative F2-layer storms related to geomagnetic activity and quiet-time disturbances (Q-disturbances) belong to different classes of events and exhibit different morphology. Mid-latitude daytime Q-disturbances, unlike the usual negative F2-layer storms, demonstrate NmF2 and hmF2 inphase variations. An analysis of Millstone Hill ISR observations for usual and Q-disturbances has shown the difference in the controlling aeronomic parameter variations for the two classes of events. The decrease in atomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Therefore their morphology, formation mechanisms and the difference from usual F2-layer storm effects may have certain interest. Some aspects of this issue have been considered by Mikhailov et al (2007b). It was stressed that negative F2-layer storms related to geomagnetic activity and Q-disturbances belong to different classes of events and exhibit different morphology with respect to: (a) hmF2 variations; (b) Ne(h) distributions; (c) seasonal and latitudinal variations of the occurrence frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore their morphology, formation mechanisms and the difference from usual F2-layer storm effects may have certain interest. Some aspects of this issue have been considered by Mikhailov et al (2007b). It was stressed that negative F2-layer storms related to geomagnetic activity and Q-disturbances belong to different classes of events and exhibit different morphology with respect to: (a) hmF2 variations; (b) Ne(h) distributions; (c) seasonal and latitudinal variations of the occurrence frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale changes in the ionosphere expressed by enhancements and/or depressions of the plasma density and electron content are recognized as the ionospheric storms (Jakowski et al, 1991;Ho et al, 1996;Mendillo, 2006;Zhao et al, 2007). It has been found that the ionosphere disturbances can either be induced by geomagnetic disturbance or occur under magnetically quiet-time conditions (Mikhailov et al, 2007). It is not known so far which kind of ionosphere perturbations are magnetically associated and which are not.…”
Section: Introductionmentioning
confidence: 99%
“…Ionospheric disturbances and day-to-day variations in ionospheric parameters are not only caused by magnetic storms, but may be also related to geomagnetic quiet conditions, ionosphere-lower atmosphere coupling, stratospheric sudden warming events, and other sources (see e.g. Goncharenko et al, 2010;Mikhailov et al, 2007;Zhao et al, 2008). Obviously, it is likely to have anomalous ionospheric changes before the occurrence of an earthquake, but it is not correct to connect these anomalies and the seismic events without further validations.…”
Section: Introductionmentioning
confidence: 95%